Genetic landscape of Parkinson’s disease and related diseases in Luxembourg - Landoulsi, Zied; Pachchek, Sinthuja; Bobbili, Dheeraj Reddy; Pavelka, Lukas; May, Patrick; Krüger, Rejko; , the NCER-PD Consortium (Frontiers in Aging Neuroscience, 2023)
Objectives To explore the genetic architecture of PD in the Luxembourg Parkinson’s Study including cohorts of healthy people and patients with Parkinson’s disease (PD) and atypical parkinsonism (AP). Methods 809 healthy controls, 680 PD and 103 AP were genotyped using the Neurochip array. We screened and validated rare single nucleotide variants (SNVs) and copy number variants (CNVs) within seven PD-causing genes (LRRK2, SNCA, VPS35, PRKN, PARK7, PINK1 and ATP13A2). Polygenic risk scores (PRSs) were generated using the latest genome-wide association study for PD. We then estimated the role of common variants in PD risk by applying gene-set-specific PRSs. Results We identified 60 rare SNVs in seven PD-causing genes, nine of which were pathogenic in LRRK2, PINK1 and PRKN. Eleven rare CNVs were detected in PRKN including seven duplications and four deletions. The majority of PRKN SNVs and CNVs carriers were heterozygous and not differentially distributed between cases and controls. The PRSs were significantly associated with PD and identified specific molecular pathways related to protein metabolism and signal transduction as drivers of PD risk. Conclusion We performed a comprehensive genetic characterization of the deep-phenotyped individuals of the Luxembourgish Parkinson’s Study. Heterozygous SNVs and CNVs in PRKN were not associated with higher PD risk. In particular, we reported novel digenic variants in PD related genes and rare LRRK2 SNVs in AP patients. Our findings will help future studies to unravel the genetic complexity of PD.